Trilha das letras no Pará: o caminho percorrido pela literatura no jornalismo paraense - SILVA, Lívea Pereira Colares da (Universidade Federal do Pará, 2017)
This study wants to understand how the newspapers Folha do Norte (1896 - 1974) and O Liberal (1946 - present) make their journalistic coverage about the nacional and regional literature. The research is a Content Analysis, an exploratory analyze on 110 years of journalistic production of these journals, from 1896 until 2006, with cutouts for ten years, and only in January and July. For the analysis, we used a protocol with the items that will help to understand how the newspapers works. That analysis will observe the origin of the books and the way how journalism acts in the routine. The survey resulted in a corpus of 588 newspaper articles about literature, and 201 published by Folha do Norte and 387 belonging to the Liberal. The protocol resulted in datas, this datas was analyzed by the historical context of the periods studied. These contexts were understood from the studies by authors such as Geraldo Martires Coelho, Vicente Salles, Nelson Werneck Sodre and Marialva Barbosa. To interpret the aspects of the journalism, such as the notion of event and genres used by the press, the research brings the study authors as Adriano Duarte Rodrigues, Jorge Pedro Sousa, Nelson Traquina, Mauro Wolf and José Marques de Melo. The intention is to understand what is the agenda and news-value when it comes to covering literary subjects and understand how this happens, what formats and genres are more used and what they say about the importance given to literature, by the press. The relevance of this study is to understand